ANALYSIS OF THE CONCEPT "TEACHING METHOD" IN THE HISTORICAL CONTEXT - Барабаш, В.І.; Скакун, В.О. (Modern engineering and innovative technologies, 2024)
The nature of activities and relationships between teachers and students, the depth and strength of acquired knowledge, skills, and abilities, as well as the extent to which it causes cognitive, emotional and practical activity of students and forms their